Do We Need Media Guidelines When Reporting on Panic Buying? An Analysis of the Content of News Reports During the COVID-19 Pandemic - Rajkumar, Ravi Philip (Frontiers in Communication, 2022)
The COVID-19 pandemic, with its attendant supply chain disruptions and restrictions on internal movement, has been associated with frequent episodes of panic buying both in its initial phase and in subsequent waves. Empirical evidence suggests that news media content and consumption are important determinants of attitudes and behavior during the pandemic, and existing research both before and during the pandemic suggests that panic buying can be influenced by both exposure to media reports and their specific content. This pilot study was conducted to assess the quality of media reports of panic buying during the second year of the COVID-19 pandemic, using two independent measures of news article quality. Seventy news reports of panic buying across twelve countries, covering the “second wave” of the pandemic from January 1 to December 31, 2021, were collected through an online search of media outlets using the Google News aggregator. These reports were analyzed in terms of the content of their reporting, based on existing research of the factors driving panic buying during the COVID-19 pandemic. Each report was scored for quality using two different systems: one based on an existing WHO guideline, and one based on the work of a research group which has published extensive work related to panic buying during this pandemic. It was observed that a significant number of reports contained elements that were likely to amplify, rather than attenuate, panic buying behavior, and that the quality of news reports was generally poor regardless of pandemic severity, cultural values, or freedom of the press. On the basis of this evidence, suggestions are offered to improve the media reporting of panic buying and minimize the risk of fear contagion and imitation.